Practical sports coaching - Nash, Christine (New York, NY : Routledge, 2022)
"Practical Sports Coaching is a thorough and engaging guide for all sports coaching students and practitioners. Drawing on real-life case studies and examples, the book is designed to develop practical coaching skills and provides readers with the methods and tools they need to become an expert coach. Structured around all facets of the coaching process, the text comprehensively covers topics such as: Preparing to Coach, the Role and Philosophy of Coaching, Coaching Environments and the use of Modern Technology in Coaching. This new and fully updated edition includes several new chapters that examine new and critical research areas such as the Coaching Professional, Coach Wellness & Mental Health and Performance Analysis for Coaches. The book's practical approach allows the reader to consider common challenges faced by coaches, suggesting solutions to performance concerns and preparing students for the realities of professional sports coaching. The contributors draw upon their practical coaching experience as well as an understanding of coach learning and development. Practical Sports Coaching helps to bridge the gap between theory and practical coaching skills, and is an essential text for coaching students looking to deepen their understanding of sports coaching and experienced coaches developing their own practical skills"--
The role of the coach / Kristen Dieffenbach and Melissa Thompson -- Planning your coaching : a focus on youth participant development / Andy Abraham, Sergio Lorenzo Jimenez Saiz, Steve Mckeown, Gareth Morgan, Bob Muir, Julian North, and Kevin Till -- The importance of a coaching philosophy / John Widdowson and John Sproule -- The coaching professional / Christine Nash -- The talent development curriculum / Jamie Taylor and Dave Collins -- The art and science of refinement : modifying, polishing and tweaking learnt skills / Howie J. Carson and Dave Collins -- Team coordination and decision making / Alan MacPherson and Chris Duncan -- The competition environment / Dave Collins and John Kiely -- Coach learning and development / Christine Nash -- Interpersonal knowledge of coaching / Koon Teck Koh and Li Quan Warrick Tan -- Coach mental health and well-being / Sebastian Altfeld, Michael Kellmann, and Jürgen Beckmann -- Moving beyond competence / Christine Nash -- Communities of practice and social learning spaces for sport coach learning : what and how / Diane M. Culver and Tiago Duarte -- Big data in sport / Jill Clark and Christine Nash -- Performance analysis for coaches / Christopher Carling & Naomi Datson -- Putting it all together : expertise in coaching / Christine Nash.
Includes bibliographical references and index.
Keywords: Coaching (Athletics)